Perfomance Standard-Compliant Secondary Control: The Case of Chile - Gutierrez-Gonzalez, E (IEEE Computer Society, 2017)
The two largest interconections in Chile (SIC and SING) are about to become interconnected. As power balance is a concern in the operation of a power system, it is important to understand the operation of AGC while systems become interconected. In this sense, the performance of the AGC systems after the interconection may change, and the new operating condition may require a change in the parameters of the AGC controllers to comply with performance standards. This work presents an analisis to determine the parameters of the AGC systems in the two interconection to comply with frequency control perfromance standards and minimize the required reserves. In the absence of a Chilean secondary frequency control performance standard, the North American standards are considered. To validate the results, empirically-validated frequency response models of SING and SIC are considered to obtain numerical results. © 2003-2012 IEEE.